An Artificial Neural Networks Model For The Estimation Of Formwork Labor - Dikmen, Ümit; Sönmez, Murat (Vilnius Gediminas Tech Univ, Sauletekio Al 11, Vilnius, Lt-10223, Lithuania, 2011)
Artificial Neural Networks (ANN) is a problem solving technique imitating the basic working principles of the human brain. The formwork labour cost constitutes an important part within the costs of the reinforced concrete frame buildings. This study suggests a method based on artificial neural networks developed for estimating the required man-hours for the formwork activity of such buildings. The introduced method has been verified in the study with reference to the test conducted involving two case studies. In all cases, the model produced results reasonably close to actual field measurements. The model is a simple and quick tool for the estimators and planners to aid them in their work.
Keywords: artificial neural networks (ANN); formwork; labour; cost; man-hour; productivity; yapay sinir ağları (YSA); kalıp; emek; maliyet; bir saatlik çalışma; verimlilik; construction productivity assessment; inşaat verimlilik değerlendirmesi